Cultureshock! : a survival guide to customs and etiquette : Czech Republic - Nollen, Tim. (Singapore : Marshall Cavendish Editions, 2005)
'CultureShock! Czech Republic allows readers to discover the rich history behind the country, from the Hapsburg era to the effect of Communism. Gain an insight into the local characteristics from the Czech love of nature to their musical inclination to their magical folklore. Be aware of social etiquette when dining in someone's home or learn what to expect when attending a traditional wedding. Navigate your way around the complex Czech language, especially its 40-lettered alphabet and sometimes difficult pronunciation. Discover what you should expect to pay for your new home, what your tenant rights are and what documents are required for obtaining a work and spousal visa. Peppered throughout with useful phrases, terms and resources, CultureShock! Czech Republic is a must-have for anyone planning on adapting to life in the Czech Republic.'--Publisher.
First impressions -- History, politics, economics and religion -- Czech characteristics -- Socialising -- Settling in -- Eating and drinking -- Entertainment and culture -- Communicating -- Doing business -- Fast facts about Czech Republic.
Includes bibliographical references (p. 280-287) and index.
Keywords: Etiquette -- Czech Republic; Czech Republic -- Social life and customs; Czech Republic -- Description and travel; Electronic books